Tinjauan Perampasan Aset dalam Tindak Pidana Pencucian Uang dari Perspektif Keadilan - Fuadi, Gumilang; Putri, Windy Virdinia; Raharjo, Trisno (Jurnal Penegakan Hukum dan Keadilan, 2024)
Money laundering is a crime that harms the public interest, causes economic instability in a country, and is more dangerous than corruption because tracking money flow from money laundering will be more difficult. When considering the impact, asset forfeiture is vital since it employs a "follow the money" strategy. This study reviews asset forfeiture in money laundering from the perspective of justice. This study is a normative or doctrinal research, also called dogmatic research, with a conceptual and statutory approach. The study shows that asset forfeiture in money laundering has been regulated in Indonesia as criminal forfeiture based on the Criminal Code and Criminal Procedure Code, civil forfeiture, and administrative forfeiture based on the PPTPPU Law. However, in its regulation and implementation, there are still legal loopholes that criminals can use to hide the proceeds of their crimes, so it has not provided a sense of justice and is detrimental to the state and society as victims of money laundering. Based on the perspective of justice rooted in the principle of fundamental justice, crime should not benefit the perpetrators. This perspective underlies the need to expand the scope of asset forfeiture arrangements, especially civil/in rem forfeiture, by reformulating the provisions in the PPTPPU Law. Furthermore, broadening coverage can be achieved by enacting laws that govern asset forfeiture. This legislation should encompass not only assets held in the user accounts of financial service providers but also all assets connected to criminal activity. Protecting good faith third parties is necessary to enhance the society and state's sense of fairness.